Evaluation Of The Group Equivalent Pile Approach For Laterally Loaded Shafts - Cheng Lin (Deep Foundations Institute, 2009)
The Group Equivalent Pile (GEP) approach was proposed by researchers to analyze a laterally loaded pile group. This approach enables engineers to evaluate the behavior of a pile group in single pile analysis software, such as LPILE. A previous study showed that the calculated results using the GEP approach for piles agreed well with field test data. To evaluate the accuracy of the GEP method for analyzing laterally loaded shafts, two case studies with different shaft diameters were performed in this study. The comparisons showed that the calculated results using the GEP method and considering the contribution of the shaft cap if embedded generally agreed with the measured from the full-scale tests.